Vehicles : experiments in synthetic psychology - Braitenberg, Valentino (Cambridge, Mass : MIT, 1986)
Foreword / Michael A. Arbib -- Introduction: Let the problem of the mind dissolve in your mind -- Getting around -- Fear and aggression -- Love -- Values and special tastes -- Logic -- Selection, the impersonal engineer -- Concepts -- Space, things, and movements -- Shapes -- Getting ideas -- Rules and regularities -- Trains of thought -- Foresight -- Egotism and optimism -- Biological notes on the vehicles. The virtues of crossed connections -- The compound eye of the fly: reconstruction of continuity in the visual representation -- Olfactory orientation: control of behavior by symmetrical reins -- Orientation and object fixation in flies -- McCulloch-Pitts neurons and real neurons -- Evolution -- Memory -- In search of an engram: the anatomy of memory -- Maps and their use -- Shapes. The morphemes of visual perception -- An inborn category of acoustic form perception -- Structure of the cerebral cortex -- Cell assemblies: embodiments of ideas -- Threshold control and the pump of thoughts.
boek